Zakat Distribution Practice of Non-Institutional Zakat Management in Bangladesh - Rahman, Md Muhibur (International Journal of Zakat, 2024)
This study examines the methods and challenges of managing zakat outside of organized institutions in Bangladesh. A qualitative and quantitative approach is used to obtain a better understanding. The research encompasses an extensive field survey of 210 participants, comprising zakat payers and recipients from six districts. It was found that most of the zakat is directly given to recipients instead of flowing through formal channels, meaning there is a tendency for personal involvement, which has almost immediate impacts. Most respondents compute their available assets to determine the proportion to pay as zakat, yet only a part understand this process. Nevertheless, despite vast differences between overall contribution and actual money received by beneficiaries, cash remains the most common mode of distributing zakat. This difference shows the challenges in allocating funds. Besides, it identifies issues regarding the government, monitors what is given out, and indicates ongoing discussions on how effective institutional or non-institutional management is. The conclusions highlight a need to improve zakat management practices involving direct and institutional methods.